Reliability of haemophilia early arthropathy detection with ultrasound (HEAD-US) in children: a comparative magnetic resonance imaging (MRI) study - Plut Domen; Kotnik Barbara Faganel; Pusnik Luka; Slak Peter; Snoj Ziga; Salapura Vladka (Radiology and Oncology, 2022)
Ultrasound (US) has been proven to be reliable in the assessment of early haemophilic arthropathy in the adult haemophilic population, however few studies so far focused on the reliability of US specifically in the paediatric haemophilic population. We were interested if the changing appearance of the growing bone hinders the ultrasonographic evaluation of the pathologic processes caused by haemophilic arthropathy. The aim of the study was to assess the reliability of US for evaluation of haemophilic arthropathy in children in comparison to magnetic resonance imaging (MRI).